Software language engineering : 4th International Conference, SLE 2011, Braga, Portugal, July 3-4, 2011, Revised Selected Papers - Aßmann, Uwe; Sloane, Anthony (Lecture Notes in Computer Science, 2012)
This book constitutes the thoroughly refereed post-proceedings of the 4th International Conference on Software Language Engineering, SLE 2011, held in Braga, Portugal, in July 2011. The 18 papers presented together with 4 tool/language demonstration papers were carefully reviewed and selected from numerous submissions. SLE's foremost mission is to encourage and organize communication between communities that have traditionally looked at software languages from different, more specialized, and yet complementary perspectives. SLE emphasizes the fundamental notion of languages as opposed to any realization in specific technical spaces.